The impact of sex and gender on aortic events in patients with Marfan syndrome. (11th May 2022) - Nucera, Maria; Heinisch, Paul P; Langhammer, Bettina; Jungi, Silvan; Mihalj, Maks; Schober, Patrick; Luedi, Markus M; Yildiz, Murat; Schoenhoff, Florian S
Abstract: OBJECTIVES: The aim of this study was to explore sex and gender differences regarding aortic events in Marfan patients. METHODS: We analysed all data from our connective tissue disorder database. Only patients with Marfan syndrome were included. For analysis, patients were divided by sex. Female patients were further divided into 2 subgroups: with versus without children. Aortic events were defined as Stanford type A aortic dissection (TAAD) or type B aortic dissection (TBAD) or any aortic intervention. RESULTS: A population of 183 Marfan patients was analysed for the purpose of this study. One hundred four (57%) were male and 79 (43%) were female patients. Thirty-seven (47%) of the 79 female patients had at least 1 child. Male patients had a significantly higher probability of experiencing an aortic event ( P  = 0.015) compared to female patients. However, there was no increased probability for recurrent events in male patients compared to female patients ( P  = 0.063). Follow-up revealed no sex and gender differences in the occurrence of Stanford TAAD or TBAD between male and female patients ( P  = 0.324/ P  = 0.534). While 11% of women with children suffered from peripartum aortic events, 24% experienced Stanford TAAD unrelated to pregnancy. CONCLUSIONS: Male patients have a higher risk of aortic events than female patients. The majority of women were not aware of their Marfan syndrome diagnosis before conceiving. One out of 10 women suffered from peripartum Stanford TAAD or TBAD. Twice as many female patients with children suffered from aortic dissection unrelated to childbirth. There were no sex and gender differences affecting mortality in Marfan patients. Abstract : Marfan syndrome (MFS) is a connective tissue disorder inherited in an autosomal dominant fashion.